Review of the surface architecture of the equine neopallium: Principle elements of a cartographic pattern of sulci revisited and further elaborated. (14th March 2018) - Lang, A.; Wirth, G.; Gasse, H.
Summary: The surface architecture of the equine telencephalon is far more complex and complicated than, for example, that of the carnivore's brain, and basic organization patterns are more difficult to recognize. This is due to species differences, to interindividual variations and even to asymmetries between right and left hemispheres. Moreover, a very heterogeneous anatomical terminology, especially in the pioneering older literature, does not allow easy access to a unanimous topographical orientation. This review article presents the key features of this heterogeneity and its anatomical and terminological backgrounds, focusing on the cerebral sulci. The abundant, often divergent data from the reviewed literature are displayed by means of graphical illustrations highlighting the key issues and comparing them with the terminology of the present Nomina Anatomica Veterinaria. These illustrations are supposed to convey the relevant conformities and discrepancies regarding locations, courses and names of cerebral sulci in an easier and more effective manner than written texts could possibly do with such a complex and heterogeneous matter. The data from the selected literature are supplemented by and discussed together with photographs and drawings of brains from our own collection. This combination of a classic review article and own findings is supposed to confirm, to further elaborate and to evaluate the key sulci serving as landmarks for an orientation on the equine neopallium. These are, laterally, the Sulcus suprasylvius, coronalis and praesylvius; dorsally, the Sulcus marginalis; and medially, the Sulcus genualis, cinguli and splenialis. Special attention is also given to the Fissura sylvia; a Fissura sylvia accessoria is proposed.